2005
DOI: 10.1021/ja045190i
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Vibrational Analysis of Single-Walled Carbon Nanotubes

Abstract: Abstract:We use near-field Raman imaging and spectroscopy to study localized vibrational modes along individual, single-walled carbon nanotubes (SWNTs) with a spatial resolution of 10-20 nm. Our approach relies on the enhanced field near a laser-irradiated gold tip which acts as the Raman excitation source. We find that for arc-discharge SWNTs, both the radial breathing mode (RBM) and intermediate frequency mode (IFM) are highly localized. We attribute such localization to local changes in the tube structure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
164
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(177 citation statements)
references
References 21 publications
7
164
1
5
Order By: Relevance
“…Ren ular adsorbates on smooth single-crystal substrates (Figure 6; 56). Anderson et al have applied TERS to study single-walled carbon nanotubes with 14-nm spatial resolution (57). These experiments demonstrate the technique's salient features, which are the ability to probe molecules on non-SERS active substrates and high spatial resolution.…”
Section: The Futurementioning
confidence: 98%
“…Ren ular adsorbates on smooth single-crystal substrates (Figure 6; 56). Anderson et al have applied TERS to study single-walled carbon nanotubes with 14-nm spatial resolution (57). These experiments demonstrate the technique's salient features, which are the ability to probe molecules on non-SERS active substrates and high spatial resolution.…”
Section: The Futurementioning
confidence: 98%
“…[1] The tip apex functions as a single 'hot' spot, which enhances the Raman scattering from the scanned sample area. At optimized conditions, single-molecule sensitivity [2] can be achieved and the spatial resolution can reach ∼10 nm, [3] making TERS an important candidate for nanoscale chemical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced (resonance) Raman spectroscopy [SE(R)RS] from a metal-coated AFM tip does not suffer from these limitations. Indeed, it has been shown that fingerprint signatures of molecules and functional groups can be obtained with this technique, in the best case with nanometer resolution (72,73). As illustrated in Fig.…”
Section: Integration Of Techniques and Perspectivesmentioning
confidence: 97%